A Physical-Chemical Study of the Interference of Ceftriaxone Antibiotic with Copper Chloride Salt - Elsayed M. AbouElleef; Mowafak M. Mahrouka; Sherine E. Salem (Bioinorganic Chemistry and Applications)
The nano-CuCl2.2H2O salt was prepared by the ball milling method. The association parameters for bulk and nano-CuCl2 salts in H2O are estimated at different temperatures using the conductivity method by applying the Fuoss–Shedlovsky equation and it was higher for nano-CuCl2 than bulk CuCl2 salt. The interaction between the cation (Cu2+) and ligand (ceftriaxone) in H2O was determined also by the conductometric method. Two stoichiometric complexes 1/2 and 1/1 (M/L) are estimated and follow the order Kf (1/1) > Kf (1 : 2) and ∆Gf (1/1) > ∆Gf (1/2) for (M : L) (in negative values) indicate the favorable of formation of (1/1) complex compared to the (1 : 2) complex. The Gibbs free energies change was increased in negative signs with increasing the temperature. The antimicrobial activities of CFT, bulk Cu-CFT complex, and nano-Cu-CFT complex were studied on LB agar by the disc diffusion technique against clinical isolates of gram-negative bacteria (Klebsiella pneumonia and Pseudomonas aeruginosa) and Fungi (Candida albicans). It was observed that (CFT) has a higher zone of inhibition and antibacterial activity than that of bulk and nano-Cu-CFT complexes in Klebsiella pneumonia and Pseudomonas aeruginosa (gram-negative bacteria). The nano-Cu-CFT complex showed a higher clear zone of inhibition and antifungal activity against candida than bulk Cu-CFT complex while the absence of the inhibition zone in CFT, so nano-Cu-CFT complex, can be used as an antifungal drug.